DINAMIKA TAFSIR SOSIAL INDONESIA - Sunarto Sunarto (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
The Qur'an is a holy book that revealed by the Most Holy. In order for the sanctity of the Qur'an to be more meaningful and relevant to (as a guide for human life, as a distinguishing between the true and the false), the Qur'an needs to be reflected in the real world. With the presence of "Social Interpretation" model, this is a step forward that needs to be appreciated, as the courage of the mufassir  in annuling the Qur’an is not limited to understanding Qur’an, but rather the mufassir actualizes the Qur’an with problems of social political development. Sometimes writing point of the writer is faced with the tip of the Lord's sword. Therein the test mufassir's guts in pouring his thoughts.